Analysis of behavioral intention on ABC system adoption: Model of information systems technology and success acceptance - Baiq Nensi Veni Indipenrian; Bambang Subroto; Aulia Fuad Rahman (Universitas Hayam Wuruk Perbanas, 2015)
This study aims to examine the effect of individual behavioral change on the adoption of activity- based costing (ABC) system and its usage, using Unified Theory of Accep-tance and Use of Technology (UTAUT) and Information System Success Model. The sample involves 78 respondents who have positions as financial manager, controller manager, accounting manager, and production manager in mid-sized manufacturing companies in East java. The data were collected by survey method. This study used a Partial Least Square (PLS) as the data analysis method. It was found that not all of the main UTAUT models were supported, because performance expectancy and effort expectancy have no effect on behavioral intention and use behavior to adopt ABC system. Whereas, social factors, information quality and facilitating conditions had a positive effect on behavioral intention and use behavior to adopt ABC system. The different results of this study with several previous studies are probably caused by the differences in the context of system, culture and characteristics of the sample. The implication of this study is not only to propose a theoretical framework for researches in future, but also useful for companies to optimize the use of ABC system that should be supported by top level and mid-level management and the readiness of the individu-als to accept the adoption of the ABC system.